Analisis Energi pada Mesin Pembeku Sebelum dan Setelah Penambahan Receiver - Paulus Sukusno; Benhur Nainggolan; Dianta Mustofa Kamal (Jurnal Mekanik Terapan, 2023)
Freezing machine is a tool that is widely used to maintain the quality of food ingredients. However, freezing technology requires more energy than other preservation technologies, therefore an energy-efficient freezer is required. The aim of this research is to study and determine the freezing process energy in a freezer using a receiver and without a receiver. This article reports a comparison of the energy used in a receiverless freezer and a receiver freezer, using R404A working fluid. Each to cool and freeze 1 kg of mass water for 180 minutes. The receiver is placed between the condenser and the filter dryer in the freezer system circuit. As a result, the freezer without a receiver has a COP of 2.55, and the highest use of electrical energy consumption is 1.90 [kWh] or the average electric power of the compressor drive is 634.4 [W]. While the use of electrical energy consumption in a freezer without a receiver is low at 1.01 kWh or the average electric power of the compressor drive is 335.7 [W]. Thus, the freezer using a receiver is 47% more efficient than a freezer without a receiver, the other result is that the water-ice temperature can reach -31oC lower than -14oC. This shows that the performance of the freezer with receiver is better than the freezer without receiver.